Building a gender-transformative extension and advisory facilitation system in Sub-Saharan Africa - Farnworth, Cathy Rozel; Colverson, Kathleen E. (2015)
Rural advisory services operate in environments structured a priori by gender relations. Women often experience weaker access to productive resources and decision-making power within the household, lower and less effective participation in community-level decisionmaking bodies, in value chain networks, and in innovation platforms. They are less often reached by extension and advisory services. This can make it difficult for women to implement their ideas and to act on recommendations. What must change if women are to not only access, but work effectively with extension and advisory services? Tackling the underlying gender relations that hamper access and implementation is a priority. To achieve this, it is useful to think of the extension and advisory services as a facilitation system rather than a service and to reconfigure it accordingly. Existing "best bet practices" can be captured, integrated, and scaled out to build an empowering extension and advisory facilitation system.